Institusionalisasi Ajaran Tasawuf dalam Gerakan Tarekat - Irfaan, Santosa (TAJDID, 2018)
This article examines the process of institutionalizing Sufism into a movement or organization of tarekat. Through a study of relevant literature, it was found that the tarekat (tharîqah) as a part of Sufism (Islamic mysticism) has developed since the 13th century, not long after the Mongolian armies conquered and destroyed Baghdad, Iraq. In its history, there have been internal excessive behaviours among the followers. Fortunately, tharîqah in some places and periods has encouraged people to be more or less innovators in struggling to fight the colonial power embracing different religions and also the Moslem people, as their protests, having cooperation with the former, the colonial power. After the Independence of Indonesia, some tharîqah activists in their articulation of political activities became functionaries of political parties. To them, power or authority was not their political barometer. It was only a means or medium of da’wah, the basic characteristics of Islam.